The effect of the number of endometrial CD138+ cells on the pregnancy outcomes of infertile patients in the proliferative phase - Li, Yuye; Yu, Shuyi; Liu, Wenjuan; Chen, Yawen; Yang, Xiaobing; Wu, Juanhua; Xu, Mingjuan; You, Guanying; Lian, Ruochun; Huang, Chunyu; Chen, Wanru; Zeng, Yong; et al. (Frontiers in Endocrinology, 2025)
ObjectiveThis study was conducted to determine the influence of the number of CD138+ cells in the proliferative endometrium on pregnancy outcomes.MethodsThis retrospective cohort study was conducted from January to August 2018. A total of 664 infertile women who were not diagnosed with chronic endometritis (CE) and who had not received the respective antibiotic treatment were studied. Immunostaining was performed for the plasmacyte marker CD138. The number of CD138+ cells was compared in the proliferative and mid-luteal phases of the same patients without antibiotic therapy. Infertile patients were separated into three groups based on the number of positive lesions [the number of high power fields (HPFs) containing no less than five CD138+ cells]: 0 (n = 474), 1-2 (n = 125), and ≥3 positive lesions (n = 104). The pregnancy outcomes of the infertile women undergoing in vitro fertilization-embryo transfer (IVF-ET) among the three groups were then compared.ResultsThere was a much higher level of CD138+ cells during proliferation than during the mid-luteal phase (P <0.0001). Pregnancy outcomes did not differ between the groups with 0 and 1-2 positive lesions. However, the ≥3 positive lesions group (P =0.006, P =0.029) had significantly lower ongoing pregnancy and live birth rates compared with the no positive lesion group. Although the 0 and ≥3 positive lesions groups showed a trend toward higher rates of clinical pregnancy (P =0.132), these differences failed to reach statistical significance. After age, body mass index (BMI), and clinical features were adjusted for, the ≥3 positive lesions group showed significantly lower live birth rates (aOR, 1.84; 95%CI, 1.08-3.15; P =0.026), clinical pregnancy (adjusted odds ratio (aOR), 1.78; 95% CI, 1.06-2.95; P =0.028), and ongoing pregnancy (aOR, 1.85; 95% CI, 1.09-3.15; P =0.024). The analysis demonstrated that the smallest number of stromal CD138+ cells suggestive of CE patients requiring treatment was defined as ≥ 3 positive lesions during the proliferation.ConclusionsDifferent diagnostic criteria for CE should be created for the proliferative and mid-luteal phases. The analysis demonstrated that the smallest number of stromal CD138+ cells suggestive of CE patients was defined as ≥ 3 positive lesions during the proliferative phase.